PENGARUH KNOWLEDGE SHARING, PENGALAMAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL COMO UMA UBUD GIANYAR - I Wayan Agus Yogi Antara; Ni Putu Ayu Sintya Saraswati; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Increasingly fierce competition requires companies to improve employee performance. Employee performance has an important role in achieving the goals of a company. Because with good employee performance, the company's goals can be achieved optimally. Based on the results of initial observations, the problem that exists at the Hotel Como Uma Ubud is a decrease in the level of employee performance, which can be proven through the level of employee absenteeism. Lack knowledge sharing, work experience, and work environment. This research was conducted at Hotel Como Uma Ubud using a population and sample of 72 employees as research respondents. The sampling technique used in this study is the Slovin method. The sample in this study using the Slovin formula is as follows: 134 / (1 + 134 x 0.08) = 72.13. The number of samples needed in this research is 72 employees. Data was collected through observation, questionnaires, and documentation. The data analysis technique used in this research is multiple linear regression analysis which is processed using SPSS version 25. Based on the results of the analysis, this study shows that knowledge sharing, work experience, and work environment have a positive and significant effect on employee performance at Hotel Como Uma Ubud so that the more knowledge sharing, work experience, and work environment within the Company, the performance at Hotel Como Uma Ubud will increase.